2013
DOI: 10.1682/jrrd.2011.10.0204
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activity during stance phase of walking: Comparison of males with transfemoral amputation with osseointegrated fixations to nondisabled male volunteers

Abstract: Abstract-A recent development in prosthetics is the osseointegrated fixation (OF), with improvements in comfort, fatigue, hip movement, and ease of prosthetic attachment reported. However, little information is available regarding muscle function. This study reports on selected gait parameters of the residual limb during the stance phase of level overground walking, focusing on muscle activity. Five males with transfemoral amputation (TFA) with OFs were recruited. Ground reaction force (GRF), lower-limb kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…The selected studies had as main objectives: to investigate the electromyographic patterns of amputees using osteo fixed prostheses 7,8 , to verify possible changes and adaptations in muscle activation after amputation and prosthetization process 5,6,12,13 , to evaluate the kinematic and electromyographic variation of the muscles during gait 4,5,13 , to describe the behavior of ground reaction force and electromyographic activation 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected studies had as main objectives: to investigate the electromyographic patterns of amputees using osteo fixed prostheses 7,8 , to verify possible changes and adaptations in muscle activation after amputation and prosthetization process 5,6,12,13 , to evaluate the kinematic and electromyographic variation of the muscles during gait 4,5,13 , to describe the behavior of ground reaction force and electromyographic activation 14 .…”
Section: Resultsmentioning
confidence: 99%
“…However, before the development and prescription of prosthetics, it is necessary to understand muscle condition after amputation and investigate its effects on life activity [4][5][6] . Although it is fundamental, there is a lack of research investigating muscle function after amputation [6][7][8] . The evaluation of the residual musculature provides valuable information about the adaptations that occur; however, its form of acquisition and reproducibility can be compromised by the absence of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Another study observed people with diabetic neuropathy to have earlier onset of activity of soleus (SO), medial gastrocnemius (MG) and semimembranosus/ semitendinosus compared to HOA 28 . Alterations in muscle activity patterns during walking have also been observed in people with transfemoral amputation 29 and individuals with cervical spondylotic myelopathy compared to healthy controls 30 . However, it is not clear what changes occur in muscle activity during walking in people with PD.…”
Section: Introductionmentioning
confidence: 91%
“…Interpretation of EMG activity is challenging, as there is high intra-individual and inter-individual variability in EMG activity patterns compared to kinematic and kinetic signals 29 . This is due to numerous muscles performing similar actions across joints, resulting in multiple sets of muscles able to perform a specific motor task rather than a single set, described by Latash 43 as the 'principle of abundance' 43 .…”
Section: Introductionmentioning
confidence: 99%
“…In [10], the walking gait cycle was divided into the stance phase and the swing phase. Murray et al [11] proposed an assistive approach without dictating the spatiotemporal nature of joint movement for the lower limb exoskeleton; a finite-state machine consisting of six gait phase states was used to govern the exoskeleton controller.…”
Section: Introductionmentioning
confidence: 99%